The Role of Non-Catalytic Region in Determining the Difference in Efficiency Between Two Cellobiohydrolases Revealed Through a Genetic Approach - Xinyuan Yan; Pankajkumar Ramdas Waghmare; Xiaoli Meng; Jianhui Zhang; Shaoming Ding; Yu Lei; Jun Yue; Guodong Liu (Journal of Fungi)
The cellulose-binding domain and inter-domain linker play crucial roles in the degradation of crystalline cellulose by cellulases. Although significant differences exist in the degradation efficiency of cellobiohydrolase I (CBH I) derived from different fungal sources, the relationship between this efficiency diversity and variations in the non-catalytic region remains poorly understood. In this study, we found significant differences in the length and amino acid composition of the linker region of CBH I derived from Sordariomycetes and Eurotiomycetes. By replacing the non-catalytic region of Penicillium oxalicum CBH I with the corresponding segment from Trichoderma reesei, the cellulose conversion efficiency of the extracellular enzyme system doubled under the same protein dosage, and the adsorption of CBH I onto cellulose was improved. While replacing only the cellulose-binding domain improved the degradation efficiency of the enzyme system, additional replacement of the linker region resulted in greater enhancement. Improved degradation efficiency due to non-catalytic region replacement was observed under various conditions, including higher cellulose substrate concentration, reduced cellulose crystallinity, use of pretreated straw as a substrate, and degradation at physiological temperature. These findings provide novel insights into the molecular mechanisms underlying crystalline cellulose degradation by filamentous fungi.